John the skeleton - Laan, Triinu, 1975- (Yonder, Restless Books for Young Readers, 2024)
"Everyone deserves a quiet, restful retirement. But for John, a newly retired classroom skeleton, life is just beginning. When John is adopted by Grams and Gramps and leaves the classroom to live on their farm, every day is an exciting new adventure: John rides in the car for the first time, makes a snow angel, scares away crooks, and becomes a source of comfort for Grams, Gramps, and their grandkids. With delightful illustrations and a charming cast of characters, John the Skeleton is a quirky, touching, and unforgettable book. Triinu Laan thoughtfully weaves aging and death into the fabric of life, crafting a tender portrait of what it means to care for one another, grow old together, and appreciate the little things" --